1997
DOI: 10.1046/j.1365-2141.1997.d01-2147.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐endothelial cell antibodies to the endothelial hybridoma cell line (EAhy926) in systemic lupus erythematosus patients with antiphospholipid antibodies

Abstract: Summary. The endothelial hybridoma (EAhy926) cell line was employed to clarify whether antiphospholipid antibodies (aPA) [lupus anticoagulant (LA), antiprothrombin antibody (aPT) and/or anticardiolipin antibody (aCL)] and antiendothelial cell antibodies (AECA) are identical, and establish whether b 2 -glycoprotein I (b 2 -GPI) is needed for reactivity of aPA to endothelial cells. Ig-G AECA was positive in 9/30 SLE patients with aPA (30 . 0%) and 10/22 SLE patients negative for aPA (45 . 5%). Ig-M AECA was posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…These results are consistent with the phenotypic variation in endothelial cells of dierent origins, and con®rm the frequent presence of autoantibodies reactive with vascular endothelium in both SLE and primary antiphospholipid syndrome. Although it is possible for anti-cardiolipin antibody and AECA to be partially cross-reacting antibodies [29], AECA is an endothelial cell-speci®c antibody and is dierent to anti-cardiolipin antibody [9,30,31]. In our preliminary immunoblotting study with membrane preparations of HMEC-1, we tested sera from seven patients with high titers of AECA in ELISA and found that AECA binds dierent molecular sizes (19,30,34,40, and 45 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the phenotypic variation in endothelial cells of dierent origins, and con®rm the frequent presence of autoantibodies reactive with vascular endothelium in both SLE and primary antiphospholipid syndrome. Although it is possible for anti-cardiolipin antibody and AECA to be partially cross-reacting antibodies [29], AECA is an endothelial cell-speci®c antibody and is dierent to anti-cardiolipin antibody [9,30,31]. In our preliminary immunoblotting study with membrane preparations of HMEC-1, we tested sera from seven patients with high titers of AECA in ELISA and found that AECA binds dierent molecular sizes (19,30,34,40, and 45 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was observed in SSc and may be mediated through CD95 (Fas) [53], although this point is controversial [54]. Another mechanism for apoptosis induction by AECA could implicate antiphospholipid antibodies, which could crossreact with AECA [55]. Antiphospholipid antibodies could interact with EC through the recognition of beta2-GPI adherent to EC surface [4].…”
Section: Induction Of Coagulationmentioning
confidence: 99%
“…Synovial cells of patients with rheumatoid arthritis (RA), collected from synovium which was resected during surgery, were used for culture. 16 …”
Section: Cell Culturementioning
confidence: 97%